Improvements of the approaches to the organization of thermomodernization on the example of bilding of the general education school - Maksimov А. (Ways to Improve Construction Efficiency, 2019)
Features of thermo-modernization which require development of separate organizational decisions are considered, among which: thermo-modernization can be carried out during different types of construction (reconstruction, major repairs, technical re-equipment), but unlike these types of construction can be carried out without suspension of operation of objects, adopted organizational and structural decisions to improve the energy efficiency of building envelope structures determine the technology of work execution and vice versa Ongoing decisions often affect the organization of the construction process, payback is provided by cost savings from the implementation of energy efficient measures, the list of output data for the design is wider than for a regular construction project and is not limited to the data of the old project or BTI data, there are no regulatory requirements for the design task and implementation of the section "Energy Efficiency", etc. The analysis of the most widespread structural and technological solutions used in thermo-modernization showed that it is impossible to make the choice of the optimal solution for an individual enclosure structure only by a direct evaluation of the physical, mechanical and technical and economic characteristics. It is proposed to choose the optimum structural and technological solution in thermo-modernization projects from all possible in two stages. In the first stage, it is necessary to reject those decisions, the implementation of which for this type of building is technically impossible or economically or technically inappropriate. The second is the assessment of structural and technological solutions on the basis of such global criteria as reliability, environmental friendliness, economy and relevant sub-criteria. The weight of the criteria and sub-criteria is determined by the method of expert judgment, taking into account the purpose of the building for which the decisions are selected. An example of the implementation of the proposed approach is given on the example of a typical project of school thermo-modernization. As a result of generalization of the most widespread structural and technological solutions, characteristics of thermo-modernization projects, requirements for energy efficiency of buildings, and those that are applied to structural and technological solutions, a set of possible criteria for selecting the optimal solutions is determined.